Poison: Medicine, Murder, and Mystery - Caroline Shackleton; Nathan Paul Turner (New YORK Cambridge University Press, 2014)
Poison has often played a part in fictional and real-life mysteries. This reader goes into the history of poison, from the everyday dangers in our food to the elaborate murders of the past.